Business tendency survey data. Where do the respondents’ opinions come from - Kalinowski, Sławomir; Kokocińska, Małgorzata (Economics and Business Review, 2015)
The article deals with the topic of business tendency survey data. The aim of the article was to research whether the respondents’ opinions reflect the variability of factors influencing the economic situation of enterprises. For the research the business tendency surveys of Central Statistical Office of Poland in 2000–2015 for manufacturing industry have been used. Based on the outcome of earlier research a general hypothesis has been assumed which states that the opinions of enterprises’3 containing qualitative variables are substantially influenced by quantitative variables which are based on the economic situation of businesses. The research has been done using the methods of time series analysis (Census II and Hodrick-Prescott filter) and the interdependence analysis method (Pearson correlation coefficient with time lags and Granger causality test).